Football as a terrain of hope and struggle: beginning a dialogue on social change, hope and building a better world through sport. Issue 5 (19th October 2016) - Forde, Shawn D.; Kota, Ayanda
Abstract: From diplomats and politicians, to the executives of sports governing bodies and non-governmental development agencies, to grassroots activists, sport – particularly football – is invariably invoked as an object of hope and a vehicle for building a better world. However, how hope is conceived by these various actors and institutions, and the better world that they imagine is often left unexamined. The purpose of this paper, a collaboration between a researcher interested in sport for development and peace and an activist involved in South African social movements and community football, is to begin an exploration of different understandings of hope and social change in relation to sport. Our aim is to demonstrate that reorienting discussions around how social change is conceptualised in different ways can result in critical understandings of how sport is currently being mobilised in various ways to affect change, and the potential alternatives that are being overlooked.